Association of a Synonymous SNP of INHA Gene with Litter Size Trait in Indonesian Thin-Tailed Sheep - Abuzahra, M.; Wijayanti, D.; Effendi, M. H.; Mustofa, I.; Munyaneza, J. P.; Eid, L. A.; Ugbo, E. N. (Tropical Animal Science Journal, 2024)
The inhibin alpha (INHA) serves as a marker for the number of fully developed ovarian follicles and plays a crucial role in regulating the secretion of pituitary FSH (follicle-stimulating hormone) and the frequency of ovulation. This study aims to examine the effect of INHA gene polymorphisms on the litter size of thin-tailed sheep. Detection of single nucleotide polymorphisms (SNPs) in the INHA gene was performed using PCR and DNA sequencing techniques. A total of 45 ewes were included in the study. Three SNPs were identified: g.236311141G>C, g.236311367G>A, and g.236311368G>A. Further investigation of the g.236311367G > A variant revealed that individuals with the GA genotype had a significantly higher litter size than those with the AA or GG genotype (p<0.05). SNPs at positions g.236311141G/C and g.236311368G/A were non-synonymous mutations resulting in amino acid changes p.A225P and V301I, respectively. Our results suggest that g.236311367G>A loci may serve as a potential molecular marker for improving the litter size trait in thin-tailed sheep.